Yellow Mangifera indica Linn. and Artocarpus heterophyllus Lam. seed starch as binder and disintegrant in paracetamol tablet formulation - Richelle Ann M. Manalo, Erna C. Arollado & , Joriza Mae M. Pellazar, Mae Pauline F. Siocson, Romeo-Luis F. Ramirez (Journal of Applied Pharmaceutical Science, 2018)
Utilization of fruit by-products offers a potential solution in minimizing the economic and environmental problems posed by these wastes. In this study, the seeds of yellow Mangifera indica Linn. and Artocarpus heterophyllus Lam. were used as sources of starch as binder and disintegrant in the formulation of paracetamol tablets. Physicochemical, binder and disintegrant properties of the isolated starches were measured and evaluated based on the United States Pharmacopeia (USP) specifications. The M. indica and A. heterophyllus seed starches were white to off-white in color, odorless, and fine in texture, with starch yields of 25.64% and 44.85%, respectively. The M. indica has elongated shape while A. heterophyllus has smaller round granules, resulting in passable to poor flowability. The lower solubility (p < 0.001), and higher swelling power (p = 0.017) and viscosity (p < 0.001) of M. indica may also be due to its larger, rod-shaped granules relative to A. heterophyllus. The isolated starches conformed to the USP specifications of identification, loss on drying, pH and limit of iron of official starches. Furthermore, both displayed acceptable average tablet weight, thickness, hardness, friability, disintegration time, dissolution and potency when used as binder and disintegrant in tablet formulation based on the USP acetaminophen (paracetamol) monograph. In conclusion, the starch isolated from yellow M. indica and A. heterophyllus seeds met the acceptance criteria of the physicochemical tests for starch and quality control tests for the USP acetaminophen (paracetamol) tablets. Hence, they can be used as economical and alternative sources of starch for pharmaceutical use.
Keywords: Richelle Ann M. Manalo, Erna C. Arollado, Joriza Mae M. Pellazar, Mae Pauline F. Siocson, Romeo-Luis F. Ramirez